The Influence of Student Conditions on Learning Motivation of MSDMA Study Program Students Class of 2022, STIALAN Jakarta Polytechnic - Dava Kayla Raihan Lutfi; Dian Indriyani (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
The phenomenon observed in STIALAN Jakarta Polytechnic students is that there are fluctuations in students' physical condit ions such as fever, stomach ache, coughs and colds, use of glasses, even requiring hospitalization. Apart from that, psychological conditions such as confusion, economic problems, family problems, romantic problems are factors that cannot be ignored in the teaching and learning process. The aim of this research is to identify whether there is an influence of physical and psychological conditions on learning motivation. This research applies quantitative methods using SPSS version 27 software. The focus population is students registered in the MSDMA study program class of 2022, and the research sample is 30 students. The research sampling technique used random sampling. From the results of this research, it can be seen that there is a correlation between the condition of students and the learning motivation they have in the MSDMA Study Program Class of 2022 STIALAN Polytechnic Jakarta.